REVIEW OF MEDICAL RECORD DISCLOSURE FOR RESEARCH PURPOSES AT CITRA HUSADA HOSPITAL, PANGKALAN BUN, IN 2022 - Dyah Cahyanti, Della; Astuti Setijaningsih, Retno; Prasetya, Jaka; Suyoko, Suyoko (VISIKES, 2024)
Medical records can be used for health research purposes. However, their disclosure must follow established procedures and adhere to patient data confidentiality principles. This study aims to examine the implementation of medical record disclosure for research purposes. The research method used is qualitative. The study was conducted from May to June 2022 in the medical record department of Citra Husada Hospital, Pangkalan Bun. Data were collected through observation and interviews. The data were analyzed descriptively and presented narratively. The findings revealed that Citra Husada Hospital, Pangkalan Bun, has established regulations regarding the disclosure of medical records for research purposes. The Standard Operating Procedure (SOP) for medical record disclosure aligns with the provisions of Minister of Health Regulation No. 24 of 2022 concerning Medical Records, which stipulates that medical record disclosure must be addressed to the head of the healthcare facility. Parties involved in medical record disclosure include the director, administration department, training department, and medical record department. The form of information provided is tailored to the researcher's needs with anonymized identities. To maintain the confidentiality of medical record data, Citra Husada Hospital, Pangkalan Bun, mandates that disclosure be conducted solely within the medical record room. However, field implementation does not involve accompaniment. It is recommended that medical record personnel accompany researchers when accessing medical records to minimize the risk of data breaches unbeknownst to the hospital.